Nephron-sparing surgery for retroperitoneal sarcomas - A. B. Ryabov; A. V. Chaika; V. M. Khomyakov; O. A. Alexandrov; A. K. Kostrygin; D. D. Sobolev; G. S. Pogosyan; S. V. Arzumanov; N. V. Vorobyov; V. V. Cheremisov; A. B. Utkina; S. A. Aksenov; et al. (Сибирский онкологический журнал)
Objective: to clarify the indications for the use of nephron-sparing technologies in surgical treatment of patients with retroperitoneal sarcomas. Material and Methods. The study included 64 patients with primary retroperitoneal sarcomas with kidney and renal pedicle invasion, who underwent surgical treatment in the Thoracic-abdominal Department of the P.A. Herzen Moscow Oncology Research Institute from 2010 to 2021. Twenty-one patients underwent nephrectomies, and 43 patients underwent nephron-sparing surgery. The morphological profile of sarcomas, age and gender of the patients, feasibility of using nephron-sparing technologies, postoperative complications, and long-term outcomes in patients of both groups were analyzed. Results. Forty-three patients with primary retroperitoneal sarcomas with invasion of the renal parenchyma, ureter, and renal pedicle underwent nephron-sparing surgery (precision mobilization of the kidney, ureter and vascular structures of the kidney from tumor tissue, kidney resection, ureteral stenting, resection of the renal vein orifices, resection of the ureters, and kidney autotransplantation). Postoperative complications were observed in 19.0 % of nephrectomy group patients (4 pts: II, IIIB, IV and V types according to Clavien–Dindo) and in 30.2 % of nephron-sparing group patients (15 pts: types II – 8, IIIA – 1, IIIB – 3, IV – 1). No statistical differences in the relapse-free period and survival time between two groups were observed. The 1-, 3- and 5-year survival rates were 84.1 %, 65.9 %, and 51.4 %, respectively. Multifactorial analysis showed that mortality increased significantly in patients over 64 years of age and was associated with both disease recurrence and concomitant pathology (p=0.009). There was also a trend toward decreased survival in patients with leiomyosarcoma (p=0.066). Conclusion. In retroperitoneal sarcomas, tumor resection with preservation of organs and structures not directly invaded by the tumor is the optimal surgical strategy. Nephron-sparing technologies do not worsen both immediate and long-term treatment outcomes. For leiomyosarcoma, tumor resection with nephrectomy is the most suitable approach.